DINAMIKA KONTESTATIF DALAM REPRODUKSI IDENTITAS BUDAYA JAWA DELI - Khairani, Leylia (Scenario (Seminar of Social Sciences Engineering and Humaniora), 2021)
This article emphasizes that the contestation of the Javanese Deli identity is to understand how Javanese (ex) contract coolies who were former contract workers living in plantation barracks then shifted and moved to the suburban areas of the plantation which were socially and culturally controlled by the Malay community. . By using the cultural concept of Williams (1981), which is mainly related to the efforts of the working class to actively construct culture in everyday meanings which include values, norms and material / symbolic objects, identity is not something that is given and unites in the community. certain, but always constructed. In the construction process, a battle for meaning ensues. The struggle (contestation) in building this identity is represented through social and cultural relations to emphasize the individual and social position of a community in front of other people or communities. Identity is a self-representation through which a person or society sees itself and how others see them as a socio-cultural entity.